Beyond Risk: How the Z Generation Resist the Temptation of Online Games - Sri Ayu Evianti; Dien Vidia Rosa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The increasing prevalence of online gaming has raised concerns about potential challenges facing students, particularly regarding mental health, financial stability, and economic implications. For Generation Z, online games have become a significant avenue for engaging in the informal economy, with gambling emerging as a prominent aspect facilitated by technological advancements. This study investigates how Generation Z navigates the allure of online gaming, resists temptations, and manages associated risks. Drawing upon Ulrich Beck's Risk Society theory and employing ethnographic methods, the research examines the decision-making processes of Generation Z players. Data collection involved interviews with respondents in various settings, supplemented by existing research in the field. The findings highlight several key issues, including the temptations of social media integration, peer influence, and financial gains, as well as the risks of accumulating debt and developing dependencies on gaming for entertainment and monetary rewards. These challenges pose significant implications for the mental well-being of Generation Z individuals.